Robust Evaluation of Reference Tilt in Digital Holography - Xu, Xianfeng; Wang, Hao; Sheng, Hui; Luo, Weilong; Wang, Xinwei (Applied sciences, 2022)
A robust approach is designed to evaluate the reference tilt angle (RTA) accurately and efficiently by local Gaussian fitting (LGF) for the distribution of one frequency peak on a spatial spectrum plane (SSP). The novel method proposed can avoid enlarging the data array on either a hologram or an SSP and then alleviate the computing burden on information processing hardware. Moreover, the RTA precision can be improved by one order of the magnitude in certain ranges, which benefits not only the accurate image recovery in an off-axis digital holography (DH) display but also the thorough removal of the tilt error effect on the image quality in phase-shifting digital holography (PSDH). The error source of the frequency peak position is analyzed theoretically and the principle with detailed steps is described. Several cases of numerical simulations have been carried out to demonstrate the availability and accuracy of this robust RTA evaluation method.